MODULE DEVELOPMENT IN HOTS-ORIENTED IPS SUBJECTS BASED ON INQUIRY AT SMP NEGERI 7 PURWOKERTO - Ardyansah, Nopidha (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This study aims to (1) Determine the feasibility of social studies subject modules; (2) Knowing the responses of teachers and students after using the Inquiry-Based HOTS-Oriented Social Studies Learning Module; and (3) Knowing the effectiveness of using the Inquiry-Based HOTS-Oriented Social Studies Learning Module. This type of research is development research (Research and Development) with the following steps: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trials, 8) usage trials, 9) product revisions and, 10) mass production. The subject of the study was a class VIII student of SMP Negeri 7 Purwokerto. The data collection techniques used are interviews, documentation, and questionnaires. The collected data were analyzed by qualitative and quantitative descriptive analysis. The effectiveness test was carried out with pretest experiments-posttest control group design. The results showed that the expert assessment of the module showed that the module was feasible to use with a percentage of 75% valid, while the effectiveness test with an n-gain value showed an effective category of 0.5502 > 0.07. Thus, the IPS module is worth using.